Analysis of the thermodynamic efficiency of a theoretical multi-stage compressor with the combined use of adiabatic, isothermal and subisothermal compression processes - V. L. Yusha (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
A thermodynamic analysis of compression processes with intensive heat removal is presented under the assumption that it can be realized with a polytropic index less than 1. A terminological classification of polytropic processes is proposed, including the concept of a subisothermal process. A method has been developed for determining the polytropic index of a subisothermal process under theoretical combined multi-stage compression, as well as methods for comparative assessment of the energy efficiency of various options for theoretical combined multi-stage compression and the thermal load on heat exchange equipment. A comparative thermodynamic analysis of various options for theoretical multistage compression with the combined use of adiabatic, isothermal and subisothermal stages has been performed. The results obtained suggest that, theoretically, from the point of view of thermodynamic efficiency criteria, combined multistage compression is preferable to multistage adiabatic compression. The prospects for the practical use of subisothermal stages as part of multi-stage compressor units are determined by the possibilities of their constructive implementation.